Iron achieves noble metal reactivity and selectivity: highly reactive and enantioselective iron complexes as catalysts in the hydrosilylation of ketones - Bleith, Tim Manuel; Wadepohl, Hubert; Gade, Lutz H. (Journal of the American Chemical Society, 2015)
Chiral iron alkyl and iron alkoxide complexes bearing boxmi pincers as stereodirecting ligands have been employed as catalysts for enantioselective hydrosilylation reactions with unprecedented activity and selectivity (TOF = 240 h-1 at −40 °C, ee up to 99% for alkyl aryl ketones), which match the performance of previously established noble-metal-based catalysts. This shows the potential of earth-abundant metals such as iron for replacing platinum—metals without any drawbacks for the reaction design.